The glory of the Son of Man in Revelation 1-3. Reflections on mysticism in the New Testament - P. G. R. de Villiers (Acta Theologica)
This article focuses on the mystical nature of the Christophany in Revelation 1-3 in order to illuminate the present research on mysticism in the New Testament. It firstly introduces the relevant text and outlines the extraordinary, exalted nature of the Christophany in Revelation 1. The second part then explains the vision in terms of the mystical revelation of hidden knowledge, whilst the third part analyses the mystical glory of the Son of Man. The article concludes with an explanation of the function of this mystical picture of Christ and the way in which a mystical Christology illuminates the relationship of believers with the divine.